Financial inclusion and companies' default risk - Tunde, Matemilola Bolaji (University of Westminster, 2024)
Financial inclusion makes access to formal financial services easy and could raise the revenue and deposit base of banks which in turn allow companies to have more access to bank credits. Regrettably, based on World Bank Report in 2022, almost 1.7 billion adults are excluded from financial services worldwide, mainly in developing nations. Besides, fewer adults own accounts in the formal financial institutions and most of them save money using informal methods. Moreover, based on S & P Global Ratings in 2023, global corporate default has been rising in several developing nations exposing companies to default risk. This paper specifies a dynamic panel model and examine the impact of financial inclusion (i.e., access to credits) on companies’ default risk in sixteen developing nations. The two-step system generalized method of moments results reveal that financial inclusion has a significant negative impact on companies’ default risk in the full sample. Moreover, financial inclusion has a significant negative impact on companies’ default risk in the three regional sub-samples. The results are also robust to different estimation methods. The results suggest that financial inclusion initiative that increase companies access to bank credits to fund profitable investments decrease default risk.